Effects of fertilization on soil nematode communities in an alpine meadow of Qinghai-Tibet plateau - Qi, Yanwen; Sun, Xinhang; Peng, Sichen; Tan, Xiaodan; Zhou, Shurong (Frontiers in Ecology and Evolution, 2023)
Nitrogen and phosphorus are essential nutrient elements and have a significant impact on above-ground plant vegetation, below-ground biotic communities, and abiotic soil factors. Soil nematodes are an important component of the soil food web, and many studies have explored the effects of anthropogenic disturbances such as grazing and fertilizer application on soil nematode species diversity. However, we know little about the mechanisms that control the response of soil nematode communities to fertilizer application. In this study, we investigated and analyzed the relationships between soil nematode species diversity, multiplicity, functional diversity, root functional traits, soil physicochemical properties, and plant species diversity under different fertilization treatments (nitrogen fertilizer, phosphorus fertilizer, and nitrogen and phosphorus fertilizer co-application) in an alpine meadow on the Tibetan Plateau. We found that (1) nitrogen fertilization significantly increased the abundance and richness of bacterivorous nematodes and nematode species diversity; phosphorus fertilization significantly decreased total nematode abundance and plant-feeder nematode abundance, while the co-application of nitrogen and phosphorus fertilizer significantly decreased the abundance and richness of bacterivorous nematodes, the abundance, and richness of omnivore-predator nematodes, and the total species diversity of soil nematodes; (2) soil physicochemical properties and functional characteristics of the root system had significant effects on soil nematode species diversity; and (3) phosphorus addition directly reduced total nematode abundance, and nitrogen and phosphorus fertilizer co-application indirectly influenced nematode abundance by inducing changes in aboveground plant species diversity and soil physicochemical properties. This study emphasizes that the species diversity and functional diversity of soil nematodes are influenced by the functional traits of root systems and by soil physicochemical properties. Our findings enrich the study of soil nematode diversity and provide a deeper understanding of the correlation between subsurface soil environment, root systems, and soil nematodes by further exploring the response mechanisms of subsurface ecosystems to fertilization and improving the scientific basis for the management of alpine meadows on the Tibetan Plateau.